2015
DOI: 10.1021/ja5114672
|View full text |Cite
|
Sign up to set email alerts
|

Eight-Membered Ring-Containing Jadomycins: Implications for Non-enzymatic Natural Products Biosynthesis

Abstract: /npsi/ctrl?action=rtdoc&an=21275442&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=21275442&lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 29 publications
(57 reference statements)
3
56
2
Order By: Relevance
“…The E-ring present in the jadomycin angucyclic framework arises from a rare spontaneous biosynthetic step involving the incorporation of an amino acid. This chemistry enables a strategy for facile derivatization of the jadomycins using culture media containing a single amino (Jakeman et al, 2005, 2009b; Robertson et al, 2015). Recently, as a result of genome analysis a number of natural products have been discovered from S. venezuelae ISP5230, including gaburedin (Sidda et al, 2014), venezuelin (Goto et al, 2010), forxymithine (Kodani et al, 2015), (+)-isodauc-8-en-11-ol (Rabe et al, 2015), and venemycin (Thanapipatsiri et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The E-ring present in the jadomycin angucyclic framework arises from a rare spontaneous biosynthetic step involving the incorporation of an amino acid. This chemistry enables a strategy for facile derivatization of the jadomycins using culture media containing a single amino (Jakeman et al, 2005, 2009b; Robertson et al, 2015). Recently, as a result of genome analysis a number of natural products have been discovered from S. venezuelae ISP5230, including gaburedin (Sidda et al, 2014), venezuelin (Goto et al, 2010), forxymithine (Kodani et al, 2015), (+)-isodauc-8-en-11-ol (Rabe et al, 2015), and venemycin (Thanapipatsiri et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although production of a jadomycin analogue with the appropriate m/z for L-lysine incorporation was confirmed by LC-MS/MS analysis of the crude growth media, 19 attempts to isolate the product using standard methodologies successfully employed for other jadomycins or by chemical derivatization were unsuccessful due to compound instability. 15,20 During investigations of crude fermentation extracts, we identified an intriguing unknown amber-colored compound by TLC that proved to be sufficiently stable for isolation and characterization. Herein, we report the isolation, characterization, and cytotoxic evaluation of the new phenanthroviridin analogue L-digitoxosyl-phenanthroviridin (1).…”
mentioning
confidence: 99%
“…It was found that it was beneficial to derivatize the crude jadomycin extract, as has been previously described, 6,11 to reduce breakdown of the derivatives during the purification process. Reaction progress was monitored by thin layer chromatography (TLC), observing the disappearance of 1 (R f = 0.25, 5:5:1 CH 3 CN/EtOAc/H 2 O) with the formation of a new band at a higher R f (see SI).…”
Section: ■ Results and Discussionmentioning
confidence: 74%
“…HMBC correlations were observed from H3a to a signal at approximately 55 ppm, which was assigned as C1. The chemical shift for H1 (3.34 ppm) is different from those of recently isolated eight-membered-ring structures (∼4.5 ppm) 11 and past oxazolone-ring-containing jadomycins (∼5.0 ppm), 5 and the origin of this difference remains unclear. Rotating frame Overhauser effect spectroscopy (ROESY) NMR was also conducted to confirm through-space interactions.…”
mentioning
confidence: 58%
See 1 more Smart Citation